Safety and effectiveness of CIMAvax-EGF administered in community polyclinics - Ortiz Carrodeguas, Ramón A.; Lorenzo Monteagudo, Geidy; Guerra Chaviano, Pedro P.; Álvarez Montané, Irene; Salomón Saldívar, Eva E.; Lobaina Lambert, Leonardo; Camacho Sosa, Kirenia; Bermúdez Pino, Raúl; Blanco Mustelier, Poncio; Valdés Rodríguez, Elba; González Piloto, Shairis; Guerra de la Vega, Arelys; et al. (Frontiers in Oncology, 2024)
In spite of the advances of immunotherapy and targeted therapies, lung cancer continues to be the leading cause of cancer-related death. The Epidermal Growth Factor Receptor is an established target for NSCLC, and its overactivation by the ligands can induce accelerated proliferation, angiogenesis, metastasis as well as proinflammatory or immunosuppressive signals. CIMAvax-EGF is an EGF depleting immunotherapy which is approved for the treatment of NSCLC patients in Cuba. The study was designed as a Phase IV trial, to characterize the safety and effectiveness of CIMAvax-EGF in advanced NSCLC patients, treated in 119 community polyclinics and 24 hospitals. CIMAvax-EGF treatment consisted on 4 bi-weekly doses followed by monthly boosters. Overall, 741 NSCLC patients ineligible for further cancer-specific treatment were enrolled. CIMAvax-EGF was safe and the most common adverse events consisted on mild to moderate injection site reactions, fever, chills, tremors and headache. For patients completing the loading doses, the median survival was 9.9 months. For individuals achieving at least stable disease to frontline and completing vaccination induction, the median survival was 12 months. Most of the functional activities and symptoms evaluated through the QLQ-C-30 EORTC questionnaire improved overtime. In conclusion, this real-world trial demonstrated that CIMAvax-EGF was safe and effective in patients that were vaccinated in the maintenance scenario. Larger effect was seen in subjects with poor prognosis like those with squamous tumors and high EGF levels. Remarkably, this community-based intervention was very important because it demonstrated the feasibility of treating advanced lung cancer patients with an active immunotherapy in primary care institutions. In addition to CIMAvax-EGF, patients received the supportive care at the community clinic. Vaccine administration by the family doctors, at the polyclinics reduced the patients´ burden at the medical oncology services, that continued affording chemotherapy and other complex therapies. We conclude that community polyclinics constitute the optimal scenario for administering those cancer vaccines which are safe and required prolonged maintenance, in patients with advanced cancer, despite the continuous deterioration of their general condition.